LENTERA EDUKASI LIFE SKILLS BAGI KOMUNITAS INKLUSIF PEREMPUAN KOLOK DI DESA BENGKALA - Sugihartha, I Wayan; Budiarta, I Nengah Edi; Kristina, Ni Puti Devi; Kristiani, Kadek Sinta; Ardana, I Ketut Satria (Sehati Abdimas, 2023)
ABSTRACTBengkala Village is known as an inclusive village for the deaf and mute community, with approximately 1.5% of its population being individuals with kolok disabilities. The majority of the kolok community members belong to the Poor Household Group, with an average monthly family income of Rp.1,448,000. Some of the challenges faced include low basic literacy and numeracy skills, limited entrepreneurial competence, digital literacy, and life skills, lack of appreciation for arts and culture, as well as high rates of early marriage. In addressing these issues, a solution is proposed, namely the Lentera Edukasi Life skills program for the Inclusive Kolok Women's Community in Bengkala Village. This program aims to enhance women's knowledge, attitudes, and skills related to literacy and numeracy, art appreciation, health, life skills, and information technology proficiency. The implementation of this Student Affairs (PPK) Ormawa uses the PALS method, which consists of awareness-raising, capacity-building, mentoring, and institutionalization stages. The target community groups are the inclusive kolok women in Bengkala Village, divided into two study groups. Activities include seminars, training, and workshops, with reference to the CREAM quality standard success indicators.The outcomes of this program include soft skills development books, curriculum, syllabi, teaching materials, as well as scientific publications and mass media publications. Thus, this program is expected to make a positive contribution to improving the quality of life and skills of inclusive kolok women in Bengkala Village.Keywords: PPK Ormawa, Bengkala Village, women's kolok, Education, Training